Optimizing Hybrid Cloud Database Architecture: Integrating SQL Server and MongoDB in Azure Environments - Achanta, Padma Rama Divya (International Journal of Scientific Research and Management (IJSRM), 2024)
This study explores the optimization of hybrid cloud database architectures by integrating SQL Server and MongoDB within Azure environments, focusing on the specific benefits and challenges of such an approach. Hybrid cloud architectures are increasingly adopted by organizations seeking flexibility, scalability, and improved data management. By examining the integration of SQL Server’s relational database structure with MongoDB’s NoSQL capabilities, this study aims to demonstrate how businesses can achieve efficient data synchronization, enhanced security, and improved performance within the Azure cloud platform. Through a comprehensive review of existing literature, analysis of case studies, and discussion of best practices, this paper provides actionable insights for organizations considering hybrid database solutions. Key findings indicate that optimizing hybrid cloud architectures with SQL Server and MongoDB can offer substantial benefits for diverse applications, but also presents unique challenges that must be managed through strategic planning and robust architecture design. This research draws on studies and publications from U.S. journals to provide a contemporary perspective on hybrid cloud database optimization.